AUTOIMMUNE DISORDERS IN CARDITIS IN CHILDREN - Gulasar K. Yusupova; Dilfuza T. Ashurova (International Scientific and Current Research Conferences, 2022)
This article discusses autoimmune disorders in carditis in children. Antibodies to denatured (single-stranded) DNA are not specific to certain diseases and are the main components of most nuclear antibodies. Despite the fact that various explanations can be given for the detection of autoantibodies, there is no doubt that they serve as markers of the autoimmune process and are of great diagnostic value.